2006
DOI: 10.1176/appi.psychotherapy.2006.60.1.1
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship among Shame, Guilt, and Self-Efficacy

Abstract: The perception of the self has been one of the fundamental constructs in psychotherapy, with attention devoted to shame, guilt, and, more recently, one's perception of ability to influence a situation-that is, self-efficacy; however, the relationship between these constructs merits scholarly attention. In the present study, researchers analyze the survey responses of 194 college students to determine relationships between shame and guilt as measured by the Test of Self-Conscious Affect (TOSCA 3, Tangney & Dear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
1
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(52 citation statements)
references
References 16 publications
0
48
1
3
Order By: Relevance
“…Shame is a complex emotion that is experienced as a painful, self-focused affect Parker, 1998) and, like hypersexuality, has been correlated with several manifestations of psychopathology including anxiety, depression, somatization, obsessive-compulsive disorders, aggression, interpersonal sensitivity, substance-related disorders, post-traumatic stress disorders, diminished self-effi cacy, violence and low self-esteem (e.g., Baldwin, Baldwin, & Ewald, 2006;Brown, 2004;Gilbert, 2000;Harder, 1995;Lewis, 1971Lewis, , 1987Nathanson, 1992Nathanson, , 1994Tangney & Dearing, 2002). Shame has also been observed among borderline patients who exhibit patterns of sexual impulsivity (Rizvi & Linehan, 2005).…”
Section: Shame and Hypersexual Behaviourmentioning
confidence: 99%
“…Shame is a complex emotion that is experienced as a painful, self-focused affect Parker, 1998) and, like hypersexuality, has been correlated with several manifestations of psychopathology including anxiety, depression, somatization, obsessive-compulsive disorders, aggression, interpersonal sensitivity, substance-related disorders, post-traumatic stress disorders, diminished self-effi cacy, violence and low self-esteem (e.g., Baldwin, Baldwin, & Ewald, 2006;Brown, 2004;Gilbert, 2000;Harder, 1995;Lewis, 1971Lewis, , 1987Nathanson, 1992Nathanson, , 1994Tangney & Dearing, 2002). Shame has also been observed among borderline patients who exhibit patterns of sexual impulsivity (Rizvi & Linehan, 2005).…”
Section: Shame and Hypersexual Behaviourmentioning
confidence: 99%
“…In our case, stigmatization and victim blaming is of serious concern as Ford et al (2013b) have found plain packaging to induce and intensify feelings of shame and disgust. Such feelings undermine self-efficacy beliefs (Baldwin et al, 2006), which is detrimental as self-efficacy beliefs are an important predictor of successful behaviour change such as smoking cessation (O'Leary, 1985;Bandura, 2010). Furthermore, one study found stigmatization as a tool of tobacco de-normalisation to exacerbate health inequalities by having counter-productive effects amongst disadvantaged smokers, who represent the majority of all smokers (Bell et al, 2010).…”
Section: Unintended Side Effectsmentioning
confidence: 99%
“…In diesen konnte mehrfach eine stärker ausgeprägte Dysfunktionalität von Schamneigung gegenüber Schuldneigung belegt werden. Studenten mit hoher Schamneigung beispielsweise zeigen eine geringe Selbsteffizienzerwartung [Baldwin et al, 2006], neigen zu höherer Selbstbeschuldigung, aber auch zu einer stärkeren Neigung, ihren Mitmenschen Schuld zuzuweisen [Lutwak et al, 2003]. Neben der Tendenz, dass Schamneigung eher mit dysfunktionalen kognitiven Strukturen einhergeht, zeigt sich auch, dass im Allgemeinen Frauen eine höhere Schamneigung haben als Männer [z.B.…”
Section: The Significance Of Shame In Different Diagnosis Groups Witunclassified